TAILORING ARCHITECTURE IN WHEAT BY MANIPULATING GENES IN BRASSINOSTEROID PATHWAY - gill, manpartik (2023)
Due to increasing human population growth it is predicted that wheat yields will need to increase by 60% by 2050. Overwhelming evidence suggests that during grain filling wheat yield potential is sink-limited, as carbon accumulation is limited by the storage capacity of the grains. Therefore, strategies to improve grain number is one of the most important avenues in the genetic improvement of yield potential. A strategy for increasing grain number is to increase the spike density within the crop. This can potentially be achieved by altering canopy architecture to improve radiation use efficiency and allow a higher planting density. Brassinosteroids (BRs) are phytohormones that have an important role in controlling architecture and assimilate partitioning. It is well established that lesions in the BR biosynthesis and signalling pathway can produce more upright canopy architecture in cereals. For example, partial suppression of the OsBRI1 gene in transgenic rice confers a beneficial erect-leaf phenotype that increases grain yield under higher planting density. Based on studies in other cereals, we targeted TaBRI1, which encodes the BR receptor, and the BR-biosynthesis genes TaDWF1 and TaDWF4 as candidates for gene characterisation and mutation in wheat. TILLING and EMS mutagenesis-based screens enabled identification of homoeologous loss-of-function mutations in these genes. These were then stacked in the common background Cadenza followed by backcrossing to stabilize the mutants for characterization. tabri1 mutants displayed reduced sensitivity, whereas tadwf1 and tadwf4 mutants showed hypersensitivity to external BR application. BR analysis found elevated levels of the biologically active BRs brassinolide, castasterone and 24-epicastasterone as well as the biosynthesis precursors campesterol (CR), 6-oxocampestanol (6-oxoCN), typhasterol and 6-deoxotyphasterol in the triple receptor mutant tabri1-a.1bd compared to non-mutant controls, potentially due to restricted feedback regulation because of compromised signal transduction. There was a 126-fold reduction in the level of CR in the triple tadwf1-abd mutant in which the conversion of 24-methylenecholesterol to CR is blocked. Additionally, the levels of the intermediates campestanol, 6-oxoCN and 6-deoxocathasterone were reduced in this mutant compared to non-mutant controls. No differences in BR levels could be detected in the triple tadwf4-abd mutant compared to controls. To determine the phenotype associated with these mutations in the TaBRI1, TaDWF1 and TaDWF4 genes, the mutants were grown under glasshouse and field conditions. Interestingly, tabri1-a.1b, tabri1-bd, tabri1-a.1d, with mutations in two TaBRI1 homoeologues, and the triple tadwf4-abd mutant exhibited increased leaf erectness without negative pleotropic effects on other agronomically important traits such as stem elongation and grain size both under glasshouse and field conditions. In contrast, tabri1-a.3bd and tadwf1-abd mutants showed alterations in canopy architecture coupled with negative effects on stem elongation and grain characteristics. As a strategy to understand the physiological mechanisms through which BRs control leaf angle, anatomical studies using low-vacuum scanning electron microscopy and laser ablation tomography were conducted on tadwf1-abd and tadwf4-abd mutants at the seedling stage. Reduced cell elongation in the auricle region and increased number of adaxial and abaxial sclerenchyma cell layers in the lamina joint were observed in these mutants compared to Cadenza. Taken together, we established the role of BR pathway genes i.e., BRI1, DWF1 and DWF4 in altering above ground architecture in wheat. Leading to identification of some upright leaf angle mutants having no negative pleotropic effects on agronomically important traits which could potentially improve grain yields of wheat under dense planting density.